2006
DOI: 10.1152/ajpheart.00221.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiac contractility by muscle metaboreflex following efforts of different intensities in humans

Abstract: Accumulation of metabolic end products within skeletal muscle stimulates sensory nerves, thus evoking a pressor response termed "metaboreflex." The aim of this study was to evaluate changes in hemodynamics occurring during metaboreflex activation obtained by postexercise muscle ischemia (PEMI) after two different exercise intensities. In twelve healthy subjects, the metaboreflex was studied with the PEMI method at the start of recovery from one leg-dynamic knee extension performed at intensities of 30% (PEMI 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
73
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 42 publications
15
73
1
1
Order By: Relevance
“…The primary function of this reflex-induced blood pressure response is to restore blood flow and arterial oxygen delivery to hypoperfused muscles (29). This pressure effect is thought to be mediated by several mechanisms: 1) a vasoconstriction in the nonischemic vascular beds (8,38), 2) an enhancement in cardiac filling (14,42), and 3) an improvement in myocardial contractility (11,12,30,39). Furthermore, there is general consensus that HR does not participate in this response since the metaboreflex-induced increase in sympathetic tone occurring during PEMI is counterbalanced by the concomitant baroreflex-induced rise in parasympa- thetic activity along with the withdrawal of central command due to the cessation of exercise (8,12,16,18,26,39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary function of this reflex-induced blood pressure response is to restore blood flow and arterial oxygen delivery to hypoperfused muscles (29). This pressure effect is thought to be mediated by several mechanisms: 1) a vasoconstriction in the nonischemic vascular beds (8,38), 2) an enhancement in cardiac filling (14,42), and 3) an improvement in myocardial contractility (11,12,30,39). Furthermore, there is general consensus that HR does not participate in this response since the metaboreflex-induced increase in sympathetic tone occurring during PEMI is counterbalanced by the concomitant baroreflex-induced rise in parasympa- thetic activity along with the withdrawal of central command due to the cessation of exercise (8,12,16,18,26,39).…”
Section: Discussionmentioning
confidence: 99%
“…This additional test aimed at verifying whether or not this condition "per se" could affect hemodynamics in heart failure patients, even though we as well as others (5,11,12) have demonstrated that, in normal individuals, RCO that was not preceded by exercise was incapable of eliciting any substantial hemodynamic modifications. On a day following the PEMI and CER tests, a RCO session consisting of 12 min (i.e., the same duration as the PEMI and CER tests) was applied: after 6 min of resting, 3 min of regional circulatory occlusion of the arm was applied followed by 3 more min of rest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the reflex is selectively activated in humans by postexercise muscle ischemia (PEMI) after isometric handgrip exercise, the pressor response occurs mainly via peripheral vasoconstriction; CO remains at the resting level (16,27,31,44,57). However, humans can also reportedly show an increase in CO during PEMI after leg cycling (5), dynamic knee extension (10), and dynamic handgrip exercise (9,11). Although differences in the type of exercise and muscle mass used in the exercise could potentially affect the results, an alternative explanation for this inconsistency is that the components of the muscle metaboreflex-mediated pressor response vary widely among human subjects.…”
mentioning
confidence: 99%
“…Third, with respect to the limitations of the model used to evoke the metaboreflex, both static and dynamic contractions followed by local circulatory occlusion increase HR, SV, and CO in humans (3,24,32) and in dogs (29), but the effects on the heart appear to be intensity-dependent (7,8,40). However, the local circulatory occlusion used to trap metabolites that activate metaboreflex prevents venous dilation, which is a major component of metaboreflex activation (10,25).…”
Section: Limitationsmentioning
confidence: 99%